IMPLEMENTASI KEBIJAKAN PENGEMBANGAN KAWASAN STRATEGIS CEPAT TUMBUH (KSCT) DI KABUPATEN PACITAN - Lestari, Santi Endah; Suryono, Agus; Domai, Tjahjanulin (JPSI (Journal of Public Sector Innovations), 2018)
Background of this research is the data founded shows disparity between north area as agroplolitan area and south area as socio cultural or tourism area. This disparity appears on poverty number in agropolitan area (north) higher than poverty number in tourism area (south). The industry number data, however, is also seen much higher in tourism area. This research is a study case and will discuss about the implementation process of policy of strategic area development in Kabupaten Pacitan. Therefore, the problems can be concluded into: How the implementation outcomes are achieved in Kabupaten Pacitan. Those, subjectives of this research are determined to understand and exhibit the KSCT implementation outcomes. The methode is using qualitatif approach with Grindle (1980) implementation model. Interactive model of Miles Huberman. And Saldana is also apllied for analysing and explaining the otucomes of implementation phenomenon. While for data collecting, some depth intreviews, document observations are elaborated to fulfil the data requirements. The result of this research is the implementation has given the positive outcomes just for south area (tourism area). While the outcomes of this KSCT implementation in the north has not been accepted by people in the agropolitan area.